REFLEXIONES SOBRE LA COMEDIA ARISTOFÁNICA - López Eire, Antonio (Myrtia, 2000)
This paper tries to demonstrate how the comedies of Aristophanes must be interpreted taking into account the fact that political and ritual features work in them together. Concerning ritual patterns, it does not impose, however, a single interpretative structure, as usually is done, but deffends the idea of Apte’s «ritual humor» and develops different structures for each play.